Analysis of macroeconomics and diagnostic of economic growth of Surabaya - Ignatia Martha (Universitas Hayam Wuruk Perbanas, 2014)
Surabaya is the second largest city in Indonesia after Jakarta. As one of the growing metropolitan city, Surabaya has great potential for investors to invest and do business. The incoming investment can lead the economy towards a more modern and improve the economic status of the city as a center for national economic growth, as well as help reduce the poverty. However, the development of which has been implemented still has many challenges, especially for the industrial sectors failed to raise and move the trade and services sector as a stimulant for other economic activities. The report further analyzes the current macroeconomic conditions and the related challenges as well as the opportunities that exist indicating that the Surabaya city developed rapidly with all the dynamics that exist in it. Surabaya city developed into the city followed by the development of the service and trade sectors with impressive property. However, the study also found some obstacles. Thus, it should be prioritized and addressed effectively to help this city grow even higher. The main barriers identified include licensing relating to the business and investment climate, transportation, human resources, and a high rate of return, especially for the middle to the bottom.